Connection Technology of HPTO Type WECs and DC Nano Grid in Island - 王坤林 田联房 游亚戈 王孝洪 盛松伟 张亚群 叶寅 (China ocean engineering, 2016)
Wave energy fluctuating a great deal endangers the security of power grid especially micro grid in island. A DC nano grid supported by batteries is proposed to smooth the output power of wave energy converters（WECs）. Thus, renewable energy converters connected to DC grid is a new subject. The characteristics of WECs are very important to the connection technology of HPTO type WECs and DC nano grid. Hydraulic power take-off system（HPTO） is the core unit of the largest category of WECs, with the functions of supplying suitable damping for a WEC to absorb wave energy, and converting captured wave energy to electricity. The HPTO is divided into a hydraulic energy storage system（HESS） and a hydraulic power generation system（HPGS）. A primary numerical model for the HPGS is established in this paper. Three important basic characteristics of the HPGS are deduced, which reveal how the generator load determines the HPGS rotation rate. Therefore, the connector of HPTO type WEC and DC nano grid would be an uncontrollable rectifier with high reliability, also would be a controllable power converter with high efficiency, such as interleaved boost converter-IBC. The research shows that it is very flexible to connect to DC nano grid for WECs, but bypass resistance loads are indispensable for the security of WECs.